Preface - den Otter, Joost (Torture Journal, 2018)
This special issue of TORTURE is meant to coincide with the twentieth anniversary of the 1994 Rwandan genocide. Annemiek Richters, Grace Kagoyire and their colleagues present a sample of stories of torture and ill-treatment, but also of rehabilitation as experienced and shared by a small group of women who survived the atrocities of this dark period of history, in which over 800,000 people were massacred. This Supplementum offers us opportunities for gaining insight on the socio-therapy approach, as well as discovering common themes that may require further research using a variety of methods. The voice of actual victims of torture has its place in a journal such as ours, and we hope this issue serves its intended purposes. Joost den Otter, phD, MD, MSc Wditor-in-Chief